2019
DOI: 10.3390/ijms20194660
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Sex Hormones in the Course of Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by T helper 2 cell (Th2)-shifted abnormal immunity, skin barrier impairment, and pruritus. The prevalence of AD in childhood is slightly higher in boys than in girls; after puberty, the sexual difference is reversed. The female preponderance in all generations exists in intrinsic AD with enhanced Th1 activity and nickel allergy, lacking increased serum IgE or filaggrin mutation. AD is often deteriorated before menstruation. We review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 120 publications
(159 reference statements)
6
60
3
1
Order By: Relevance
“…After puberty females predominate on males: respectively 8.1% and 5.7% in a study in Japan and 8.01% and 6.04% in a study in Europe and USA [24]. It was suggested that sex hormones may contribute to the higher incidence of AD-like dermatitis in female rats KFRS4/Kyo [77]. In intrinsic AD, in all generations exist a female predominance with increased Th1 activity and high incidence of nickel allergy and without filaggrin mutation or enhanced serum IgE levels.…”
Section: Atopic Dermatitismentioning
confidence: 98%
“…After puberty females predominate on males: respectively 8.1% and 5.7% in a study in Japan and 8.01% and 6.04% in a study in Europe and USA [24]. It was suggested that sex hormones may contribute to the higher incidence of AD-like dermatitis in female rats KFRS4/Kyo [77]. In intrinsic AD, in all generations exist a female predominance with increased Th1 activity and high incidence of nickel allergy and without filaggrin mutation or enhanced serum IgE levels.…”
Section: Atopic Dermatitismentioning
confidence: 98%
“…As it was reported that male AD patients have lower levels of estradiol than healthy controls [15], the immune responses of AD patients could be influenced by sex hormones. Furthermore, estrogen and progesterone enhance the activities of Th2/regulatory T cells but suppress Th1/Th17 [28]. The skin permeability barrier is reinforced by estrogen but impaired by progesterone and androgens [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, estrogen and progesterone enhance the activities of Th2/regulatory T cells but suppress Th1/Th17 [28]. The skin permeability barrier is reinforced by estrogen but impaired by progesterone and androgens [28]. Thus, the estrogen-like effect of equol may improve AD symptoms in tandem with an anti-oxidative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the innate immune system contribute significantly to the development of AD skin inflammation, including IL-5 and IL-13 from group 2 innate lymphoid cells, IL-4 from basophils, and IL-25, IL-33, and TSLP from epithelial cells (Divekar and Kita, 2015;Hussain et al, 2018;Mashiko et al, 2017;Salimi et al, 2013). This immune milieu is dependent on a patient's age, sex, and ethnic background, thereby adding to the complexity of this disease Brunner and Guttman-Yassky, 2019;Kanda et al, 2019).…”
Section: Immune Dysregulationmentioning
confidence: 99%